2016
DOI: 10.1177/0308022616656872
|View full text |Cite
|
Sign up to set email alerts
|

The association between sensory processing styles and mindfulness

Abstract: Introduction: Mindfulness is associated with psychological wellbeing and quality of life. The focus on body awareness in definitions of mindfulness suggests that an individual's sensory processing pattern may influence mindfulness abilities. Therefore, this study seeks to examine the relationship between sensory processing styles and multiple aspects of mindfulness including components of attention, awareness, and acceptance in healthy adults. Method: 151 participants, aged 18 to 60 (mean 25.24 AE 8.8), comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
(71 reference statements)
0
10
0
1
Order By: Relevance
“…Furthermore, sensory processing intervention programs could improve knowledge of it and favor self-regulation to prevent fatigue in hypersensitive populations. In fact, recent studies have mentioned the existence of some variables such as resilience, personal characteristics, and self-efficacy, as well as interventions based on mindfulness that could be trained to facilitate an increase in wellness [74,75].…”
Section: Future Researchmentioning
confidence: 99%
“…Furthermore, sensory processing intervention programs could improve knowledge of it and favor self-regulation to prevent fatigue in hypersensitive populations. In fact, recent studies have mentioned the existence of some variables such as resilience, personal characteristics, and self-efficacy, as well as interventions based on mindfulness that could be trained to facilitate an increase in wellness [74,75].…”
Section: Future Researchmentioning
confidence: 99%
“…However, the small sample size also impacted the limited number in each classified sensory pattern, meaning that these results should be interpreted cautiously as Winnie Dunn stated that "the response to sensory stimuli can be more easily understood when we study people whose sensory processing is so unusual that it interferes with even desirable life activities. The concepts involved are not as clear when studying people without a particular disorder because most people have moderate behaviors that don't stand out" (7).…”
Section: Preferencementioning
confidence: 99%
“…There was also a study that found the effectiveness of mindfulness was significantly related to sensory processing patterns classified by Adolescent/Adult Sensory Profile (AASP). (7)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body awareness has been conceptualized diversely (e.g., as interoceptive awareness, body awareness, mindfulness 17 ). Across scholars, high levels of body awareness are considered to be beneficial: Body awareness has been associated with higher ability to register body sensations 18 and with psychological well-being 19,20 . High levels of body listening and trusting have been associated with higher regulatory body-related abilities and are assumed to facilitate the management of diseases such as chronic back pain 17 ).…”
Section: Self-tracking and Body Awarenessmentioning
confidence: 99%